Cosmetic dentistry: A socioethical evaluation. (7th September 2018) - Holden, Alexander C. L.
Abstract: Cosmetic dentistry is a divisive discipline. Within discourses that raise questions of the purpose of the dental profession, cosmetic dentistry is frequently criticised on the basis of it being classified as a non‐therapeutic intervention. This article re‐evaluates this assertion through examination of ethics of care of the self, healthcare definitions and the social purpose of dentistry, finding the traditional position to be wanting in its conclusions. The slide of dentistry from a healthcare vocation towards being a predominantly business‐focused interaction between clinician and consumer conflicts with traditional notions of dentistry as a profession. Whilst it is undeniable that cosmetic dental treatment particularly lends itself to the commercial paradigm, this is not exclusive to this area of professional practice. The cultural basis of dental appearance and the potential of the dental profession to exert coercive pressure upon the public to undergo treatment that is based upon social norms is discussed. This essay concludes that cosmetic dentistry is undeniably part of the professional purpose of 21st Century dentistry. However, the caveat that may be placed upon this, is that this status is conditional upon the professional conduct of dental practitioners remaining resilient to commercial practices not compatible with professional obligations.